A-SLOTH reveals the nature of the first stars - Hartwig, Tilman; Lipatova, Veronika; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2024)
The first generation of stars (Pop III) are too dim to be observed directly and probably too short-lived to have survived for local observations. Hence, we rely on simulations and indirect observations to constrain the nature of the first stars. In this study, we calibrate the semi-analytical model a-sloth (Ancient Stars and Local Observables by Tracing Haloes), designed for simulating star formation in the early Universe, using a likelihood function based on nine independent observables. These observables span Milky Way-specific and cosmologically representative variables, ensuring a comprehensive calibration process. This calibration methodology ensures that a-sloth provides a robust representation of the early Universe’s star formation processes, aligning simulated values with observed benchmarks across a diverse set of parameters. The outcome of this calibration process is best-fitting values and their uncertainties for 11 important parameters that describe star formation in the early Universe, such as the shape of the initial mass function (IMF) of Pop III stars or escape fractions of ionizing photons. Our best-fitting model has a Pop III IMF with a steeper slope, dN/